Melacak Gen Faktor Virulensi Escherichia coli yang Tahan terhadap Siprofloksasin asal Usap Kloaka Ayam Petelur - Peranginangin, Joen Firmanta; Safika, Safika; Palupi, Maria Fatima (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
Avian Pathogenic Escherichia coli (APEC) is a cause of extraintestinal infections, particularly respiratory infections, pericarditis, and septicemia in poultry (colibacillosis). Research aimed at uncovering the virulence factors responsible for colibacillosis in poultry, especially laying hens in Indonesia, is still quite rare. The purpose of this study is to identify the virulence factors responsible for colibacillosis in E. coli strains resistant to ciprofloxacin. The virulence factors targeted in this research are the genes iss, iutA, iroN, ompT, and hlyF. The study utilized 327 E. coli isolates from the archives of the National Veterinary Drug Assay Laboratory, which were collected in 2021 in seven provinces.All isolates were tested for pathogenicity using Congo Red. Subsequently, E. coli strains determined to be pathogenic were tested for their sensitivity to ciprofloxacin using the agar dilution method. Isolates that were both resistant and pathogenic were then examined for the presence of the virulence genes using polymerase chain reaction (PCR). Based on the results of the Congo Red test, it was found that 59 isolates (18%) were pathogenic E. coli. Among the 54 pathogenic E. coli isolates subjected to sensitivity testing, 30 isolates were found to be resistant to ciprofloxacin. Subsequently, PCR analysis of these 30 ciprofloxacin-resistant pathogenic E. coli isolates revealed the presence of the iss gene in 29 isolates (96%), iutA in 23 isolates (76.6%), ompT in 19 isolates (63.3%), hlyF in 14 isolates (46.6%), and iroN in 11 isolates (36.6%). Eight isolates showed the presence of all five virulence genes, while the rest had one to three virulence genes. This study demonstrates that virulence genes are commonly found in ciprofloxacin-resistant pathogenic E. coli. This suggests a potential threat to the effectiveness of ciprofloxacin in managing colibacillosis in laying hens.